2021
DOI: 10.1038/s41598-021-88872-7
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol ameliorates high fructose diet induced hepatic steatosis in diabetic rats through modulation of lipid metabolism, inflammation, and ER stress pathway

Abstract: Excess fructose consumption contributes to development obesity, metabolic syndrome, and nonalcoholic fatty liver disease (NAFLD). Uric acid (UA), a metabolite of fructose metabolism, may have a direct role in development of NAFLD, with unclear mechanism. This study aimed to evaluate role of fructose and UA in NAFLD and explore mechanisms of allopurinol (Allo, a UA lowering medication) on NAFLD in Otsuka Long-Evans Tokushima Fatty (OLETF) rats fed a high fructose diet (HFrD), with Long-Evans Tokushima Otsuka (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 63 publications
(75 reference statements)
1
14
0
2
Order By: Relevance
“…It has been reported that ferulic acid could reduce adipogenesis, stored lipid content in adipose tissue and adipose tissue expansion, and stimulate white-fat browning via regulating the expression of related genes, revealing the anti-obesity effect of ferulic acid ( 37 39 ). We found that allopurinol, a XO inhibitor, also exerted anti-obesity capacity, which was in line with the studies of Cho et al ( 40 ) and Zhang et al ( 41 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has been reported that ferulic acid could reduce adipogenesis, stored lipid content in adipose tissue and adipose tissue expansion, and stimulate white-fat browning via regulating the expression of related genes, revealing the anti-obesity effect of ferulic acid ( 37 39 ). We found that allopurinol, a XO inhibitor, also exerted anti-obesity capacity, which was in line with the studies of Cho et al ( 40 ) and Zhang et al ( 41 ).…”
Section: Discussionsupporting
confidence: 92%
“…The circulatory lipids like FFA from adipocytes can be taken up by the hepatocytes for the synthesis of TG and other lipids, and fructose metabolism can also lead to lipid deposition in the live, bringing about non-alcoholic fatty liver and then progress to non-alcoholic steatohepatitis, fibrosis, cirrhosis, hepatocellular cancer, and liver failure (49,52,53). In the present study, we discovered that rats treated with ferulic acid and allopurinol showed less hepatic steatosis than rats in the model group, embodied in lower hepatic TG, TC, and FFA contents (Figures 3D-F), likely though suppressing de novo lipogenesis and promoting β-oxidation of FFA (26,39,40).…”
Section: Discussionmentioning
confidence: 48%
“…The IRE1α-XBP1 pathway can trigger de novo lipogenesis (DNL) by SREBP1 and its downstream genes [ 38 ]. Cho et al [ 39 ] suggested that allopurinol relieved hepatic steatosis induced by high-fructose diet through the modulation of ER stress via the IRE1 pathway. Wu et al [ 40 ] showed that Patchouli alcohol attenuated ER stress and hepatic steatosis through inhibiting the activation of PERK and IRE1 pathways in HFD-fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…The animal models disclosed that allopurinol could ameliorate insulin resistance in rats and mice. [23][24][25][26] Previous clinical research also showed allopurinol could ameliorate insulin resistance in humans. 8 The study of Fang et al included in our meta-analysis disclosed a reduced HR for T2DM associated with allopurinol use.…”
Section: Discussionmentioning
confidence: 99%